Film in the Anthropocene Philosophy, Ecology, and Cybernetics - White, Daniel (Springer International Publishing, 2018)
This book provides an interdisciplinary analysis of film in the context of the Anthropocene: the new geological era in which human beings have collectively become a force of nature. Daniel White draws on perspectives in philosophy, ecology, and cybernetics (the science of communication and control in animals and machines) to explore human self-understanding through film in the new era. The classical figure of Janus, looking both to the future and the past, serves as a guide throughout the study. Both feature and documentary films are considered. .